2015
DOI: 10.1039/c4dt03663h
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and optical nonlinearities of composite films derived from the water-soluble Keplerate-type polyoxometalate and chloroform-soluble porphyrin

Abstract: Composite films derived from the water-soluble Keplerate-type polyoxometalate (NH4)42[Mo132O372(CH3COO)30(H2O)72]·ca. 300H2O·ca. 10CH3COONH4 (denoted (NH4)42{Mo132}) and chloroform-soluble tetraphenylporphyrin perchlorate [H2TPP](ClO4)2 are successfully fabricated by a layer-by-layer self-assembly method and characterized by UV-vis spectroscopy and X-ray photoelectron spectroscopy (XPS). The structure of the {Mo132} and [H2TPP](2+) in the films remain intact in light of the results of UV-vis spectroscopy and X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…Suitable fits of the data points, corresponding to two possible 3d doublets of Mo in different oxidation states of Mo(VI) and Mo(V), were achieved using two pairs of Lorentzian–Gaussian functions. The peaks centered at 232.4 and 235.5 eV were assigned to Mo(V), while those at 233.6 and 236.6 eV were attributed to Mo(VI), respectively [ 39 , 40 ]. Semi-quantitative calculations showed that the characteristic ratio of peak area for Mo(VI) and Mo(V) was 1.45:1 for [Mo 132 ] ( Table 1 ), which was slightly over the value of 1.2 calculated from the ratio of 72 Mo(VI) to 60 Mo(V).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Suitable fits of the data points, corresponding to two possible 3d doublets of Mo in different oxidation states of Mo(VI) and Mo(V), were achieved using two pairs of Lorentzian–Gaussian functions. The peaks centered at 232.4 and 235.5 eV were assigned to Mo(V), while those at 233.6 and 236.6 eV were attributed to Mo(VI), respectively [ 39 , 40 ]. Semi-quantitative calculations showed that the characteristic ratio of peak area for Mo(VI) and Mo(V) was 1.45:1 for [Mo 132 ] ( Table 1 ), which was slightly over the value of 1.2 calculated from the ratio of 72 Mo(VI) to 60 Mo(V).…”
Section: Resultsmentioning
confidence: 99%
“…The coding sequences and preparation of major capsid protein (L1) for HPV 16 followed the procedures described in a previous work where pET-30a vector and BL21 Star TM (DE3) were employed for better expression [ 40 ]. Briefly, the recombinant Escherichia coli strain BL21 Star TM (DE3) was cultured at 37 °C with stirring at 220 rpm, where the bacteria were induced by 0.1 mM IPTG.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results show that the highly delocalized π-electron conjugation systems produced by the electron donor-acceptor of porphyrin-POM hybrid is considered to be the key to produce a strong NLO response. [183][184][185][186] [56] Copyright 2020, Royal Society of Chemistry. d) Schematic illustration of the TPI-COF with high crystallinity.…”
Section: Organic/inorganic Hybrid Porous Materials For Third-order Nlomentioning
confidence: 99%